LPS induces cardiomyocyte necroptosis through the Ripk3/Pgam5 signaling pathway. (2nd January 2021) - Fu, Guohua; Wang, Binhao; He, Bin; Feng, Mingjun; Yu, Yibo
Abstract: Necroptosis is a new type of cell death. However, the role of necroptosis in LPS-related cardiomyocyte damage has not been fully understood. The aim of our study is to explore the molecular mechanism underlying inflammation-mediated cardiomyocyte necroptosis. H9C2 cardiomyocyte cell line was treated with LPS. Then, cell viability and necroptosis were measured through qPCR and ELISA. Pathway analysis was performed to verify whether Ripk3/Pgam5 signaling pathway is implicated into the regulation of cardiomyocyte necroptosis. The results demonstrated that LPS reduced cardiomyocyte viability and activated necroptosis. At the molecular levels, oxidative stress and inflammation were triggered by LPS and these alterations may contribute to the activation of necroptosis. Finally, we found that Ripk3/Pgam5 signaling pathway was activated by LPS in cardiomyocyte and this signaling pathway may explain the regulatory mechanism underlying LPS-mediated necroptosis. Altogether, our results demonstrated that septic cardiomyopathy is associated with an activation of necroptosis through the Ripk3/Pgam5 signaling pathway.